2021
DOI: 10.1002/jcu.23080
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic value of B lines detected with lung ultrasound in acute heart failure. A systematic review

Abstract: Pulmonary ultrasound is a simple diagnostic tool with immediate results for the assessment of pulmonary congestion in patients with heart failure (HF), allowing optimization of treatment by monitoring the dynamic changes identified. We aimed to evaluate the prognostic significance of the presence of B lines detected by lung ultrasound during hospitalization for heart failure. A search was conducted for scientific articles in PubMed, Embase, Google Scholar, and Cochrane databases including clinical trials, revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Experience with LUS in assessing COVID‐19 patients shows, however, that the alterations visualized in the posterior areas are the most significant 101 . Assessing each intercostal space along its entire length is time‐consuming, so reasonably simplified protocols have been suggested for COVID‐19 patients as well, such as 18 28–55,57–151 and 14 scan protocols 24,101 . Lately one interesting study on the correlation between LUS and laboratory results also described a protocol of 12 scans (quick COVID‐19 severity index [qCSI]), 6 for each half of the chest (upper and lower areas of the anterior, lateral and posterior surfaces, respectively), for assessing the presence of B‐line and/or consolidation 152 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experience with LUS in assessing COVID‐19 patients shows, however, that the alterations visualized in the posterior areas are the most significant 101 . Assessing each intercostal space along its entire length is time‐consuming, so reasonably simplified protocols have been suggested for COVID‐19 patients as well, such as 18 28–55,57–151 and 14 scan protocols 24,101 . Lately one interesting study on the correlation between LUS and laboratory results also described a protocol of 12 scans (quick COVID‐19 severity index [qCSI]), 6 for each half of the chest (upper and lower areas of the anterior, lateral and posterior surfaces, respectively), for assessing the presence of B‐line and/or consolidation 152 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the widespread use of vertical artifacts for identification and monitoring of different pleuro‐pulmonary pathophysiological conditions, 91 , 127 , 128 we currently do not fully understand the origin of this acoustic information. 39 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recently published RCTs have demonstrated that LUS-guided treatment reduces HF-related rehospitalization in patients with HF compared with usual care ( 6 10 ), while more recent systematic reviews, including three with individual patient data, have published meta-analyses contradicting this finding and showing no effect ( 11 14 ). Based on these considerations, we believed that it would be helpful to validate the new findings by performing an up-to-date meta-analysis in an attempt to improve the precision of the estimates, reduce variability, and increase generalizability ( 39 ). As expected, the addition of the recently published RCT data, which increased the total number of participants, substantially increased the precision of the estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Basic thoracic ultrasound is a versatile and functional point-of-care ultrasound examination that may be useful in the diagnosis and management of a broad range of respiratory conditions, including pneumothorax, pleural effusion, cardiogenic pulmonary oedema, and pneumonia [1][2][3][4]. More comprehensive thoracic ultrasound examination can be performed by respiratory physicians, often needing more time and experience but potentially providing information on, for example, lymph node status and pleural pathologies.…”
Section: Introductionmentioning
confidence: 99%